DETERMINANTS AND CONSEQUENCES OF TRUST IN SOCIAL MEDIA - Maimona Noer Kamalia; Burhanudin Burhanudin (Jurnal Ekonomi, 2022)
Online shopping is currently a trend in Indonesian society. Rapid technological developments provide changes in consumer behavior in making purchasing decisions. An understanding of shopping intentions is very important to understand. This study aims to analyze the effect of guidance shopping affordance on social commerce intention and trust in social media platforms in the Indonesian context. The sampling technique used in this study is purposive sampling with the criteria that respondents have purchased products at TikTok Shop. Data retrieval was carried out online using google form with a total of 251 respondents, then data analysis was carried out using SEM (Structural Equation Modeling) analysis with Smart PLS version 3.0 to test instruments and hypotheses. The results of the study show that guidance shopping affordance is a determinant of trust in social media platforms and social commerce intention. This study further finds that social commerce intention is a consequence of trust in social media.